ANALISIS RELEVANSI SILABUS DAN SAP DOSEN PROGRAM STUDI PENDIDIKAN BAHASA INDONESIA UNIVERSITAS VICTORY SORONG - Soulisa, Irwan (Hasta Wiyata, 2018)
AbstractThis research uses the design of learning model based on the achievement of competence. This study aims to describe the level of relevance and factors that influence the development of Syllabus and SAP lecturer of the Indonesian Language Education Program at University of Victory Sorong. This research uses a descriptive-qualitative research work framework by using content analysis. Content analysis is conducted on syllabus and SAP lecturers with a reference to the learning design model based on the achievement of competence. The data collection in this research is done by interview and observation. The focus of observation in this research is to cover seven variables: identity, competency standard, basic competence, learning objectives, learning materials, source, and time. The results showed that the course of education has a relevance level of 44, 29%. In the course of linguistic has a relevance level of 42, 08%. Course of literature has a relevance level of 45, 4%. In the skill subject has a relevance level of 43, 29%. The research that has been conducted shows the relevance related to the preparation of syllabus and SAP of lecturers of Indonesian Language Education UNVIC in less relevant category. The research of syllabus and SAP lecturer based on the design of learning model based on the achievement of competence provides an illustration and benefit to the quality of service to the students to achieve the learning objectives and the preparation of the content of Syllabus and SAP lecturers well again.Keywords: Syllabus, SAP, Lecturer, Model Design Based of Competence